Kinerja IPCLN dalam Pencegahan dan Pengendalian Infeksi di Rumah Sakit: Peran Pelatihan, Motivasi Kerja dan Supervisi - Mustariningrum, Dewi Lelonowati Tri; Koeswo, Mulyatim; Ahsan (Universitas Brawijaya, Indonesia, 2015)
IPCLN (Infection Prevention and Control Link Nurse) as executor of the PPIprogram at the hospital is expected to be opinion leaders to motivate all employees andvisitors in terms of infection control. This study aims to analyze the influence of training,work motivation and supervision both partially and simultaneously to IPCLN performance.This study was an explanatory study with cross sectional survey method at March 2015 inRSUD dr. Iskak Tulungagung. Respondents are whole IPCLN as many as 35 people. Datacollection techniques using a questionnaire with Likert scale (1-5) and interviews. Descriptivedata analysis and hypothesis testing were done through multiple linear regression. Theresult were training variables (X1) with Beta coefficient = 0.362 and sig. = 0.07; workmotivation (X2) with Beta coefficient = 0.190 and sig. = 0.126; supervision variable (X3)with Beta coefficient = 0.483 and sig. = 0.001; R2 = 0,753 and value adjusted R square =0.526. The result were the training relates quite strong and significant effect on the performanceof IPCLN, motivation IPCLN no significant effect on performance, supervision isstrongly correlated with a significant effect on the performance of IPCLN. Training, motivation,and supervision related to strong and significant effect on the performance of IPCLNsimultaneously. IPCLN performance can be explained by 52.6% of the variable training,motivation and supervision simultaneously, and supervision of the dominant influence.